2017
DOI: 10.1063/1.4982009
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid predictive model for acoustic noise in urban areas based on time series analysis and artificial neural network

Abstract: Abstract. The dangerous effect of noise on human health is well known. Both the auditory and non-auditory effects are largely documented in literature, and represent an important hazard in human activities. Particular care is devoted to road traffic noise, since it is growing according to the growth of residential, industrial and commercial areas. For these reasons, it is important to develop effective models able to predict the noise in a certain area. In this paper, a hybrid predictive model is presented. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…Vehicles are predominantly sources of low and medium frequency noise, which has a high penetrating power and propagates with low dissipative absorption over long distances. The continuous growth of the car fleet has progressively increased the need for special attention to urban traffic noise, which not only increases in line with the growth of residential, industrial and commercial areas, but also causes adverse impact of noise emissions on people [7], [8]. Predicting the level of noise produced by urban transport is an essential aspect of mitigating environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…Vehicles are predominantly sources of low and medium frequency noise, which has a high penetrating power and propagates with low dissipative absorption over long distances. The continuous growth of the car fleet has progressively increased the need for special attention to urban traffic noise, which not only increases in line with the growth of residential, industrial and commercial areas, but also causes adverse impact of noise emissions on people [7], [8]. Predicting the level of noise produced by urban transport is an essential aspect of mitigating environmental pollution.…”
Section: Introductionmentioning
confidence: 99%
“…In most recent studies, hybrid models combining systems of ANN and fuzzy interference systems (FIS) (i.e., adaptive neuro fuzzy inference system-ANFIS) have been developed too [28]. Other hybrid models are represented by the integration between time series analysis techniques and ANN [29].…”
Section: Introductionmentioning
confidence: 99%
“…In order to have accurate estimation, along with statistical approaches, the nonlinear methods such as neural networks are suggested. A large number of scholars have applied the combination of statistical methods and neural networks rather than using traditional statistical methods or neural networks separately [21][22][23][24]. A majority of these researchers have found that the hybrid model could achieve more accurate results with higher R 2 (coefficient of determination) and lower level of error indexes, such as RMSE and MSE simultaneously [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%